2015
DOI: 10.1097/iae.0000000000000358
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Peripapillary Intrachoroidal Cavitation and Optic Disk Rotation

Abstract: In patients with unilateral PICCS, the eyes with PICCs had optic disks that were more spindlelike configured because of a disk rotation around the vertical axis and around the sagittal axis as compared with the contralateral eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…26,27 In this study, a peripapillary staphyloma was also found in non-highly myopic fellow eyes of the patients with unilateral high myopia. Because the refractive status or axial length is determined by the location of the fovea, peripapillary changes might be independent of the degree of myopia.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 75%
“…26,27 In this study, a peripapillary staphyloma was also found in non-highly myopic fellow eyes of the patients with unilateral high myopia. Because the refractive status or axial length is determined by the location of the fovea, peripapillary changes might be independent of the degree of myopia.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 75%
“…One can differentiate between a disc rotation around the vertical axis what leads to a perspective shortening of the horizontal disc diameter; a disc rotation around the horizontal axis, what leads to a perspective shortening of the vertical disc diameter; and a disc rotation around the sagittal axis, which does not change the perspective view on the optic nerve head and thus does not influence the two-dimensional assessment of the disc diameters. Future studies may use optic nerve head images obtained by optical coherence tomography which allows a three-dimensional assessment of the optic disc rotations and of the real disc diameters independently of a perspective distortion [ 24 ]. Fifth, the detection of a glaucomatous optic nerve appearance is generally easier in large optic discs than in small discs, if the small discs do not have cupping.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been speculated that the posterior pulling of the optic nerve sheaths on the peripapillary sclera was responsible for the presence of peripapillary intrachoroidal cavitations in highly myopic eyes due to the dehiscence between the sclera and choroid. 35,36 Other recent studies have demonstrated a phenomenon of optic nerve straightening during eye movements using MRI. In highly myopic patients, such a straightening resulted in a pulling force so strong that it retracted the eyeball within its own orbit by as much as approximately 7 mm (Demer JL, IOVS 2015;56:ARVO E-Abstract 1329).…”
Section: Stiff Optic Nerve Sheaths Increase Prelamina and Lc Strains mentioning
confidence: 99%